Pengaruh Disiplin Kerja, Motivasi Kerja, Lingkungan Kerja dan Pengembangan Karir dan Pengembangan Karir Terhadap Kinerja Guru di SD Swasta Shafiyyatul AmaliyyahMedan - Dahliana, Dahliana; R, Widi Dewi; Ningsih, Murtia (Smart Education, 2024)
A teacher's performance is measured by how well and how much they achieve their goals in carrying out their overall duties during a certain period of time. One of the 10 best private schools in Medan according to parents is Shafiyyatul Amaliyyah Private Elementary School which aims to produce a generation of Muslims with noble character, broad knowledge and superior quality. The aim of this research is to determine the influence of the work environment, work development, work motivation and work discipline on teacher performance at the Shafiyyatul Amaliyyah Private Elementary School in Medan. Sampling uses a purposive non-probability sampling technique, used in this quantitative sampling approach. Respondents in this study totaled 40 people. Based on the research results, 1) Work discipline at Shafiyyatul Amaliyyah Medan Private Elementary School does not have much influence on teacher effectiveness. There is no visible influence of work motivation on teacher performance at Shafiyyatul Amaliyyah Medan Private Elementary School. 3) The performance of Shafiyyatul Amaliyyah Medan Private Elementary School teachers, among other things, is not significantly influenced by their work environment. The impact of career development on teacher performance at the Shafiyyatul Amaliyyah Medan Private Elementary School is noteworthy. 5) At the Shafiyyatul Amaliyyah Medan Private Elementary School, work discipline, work motivation, work environment and career development simultaneously have a significant influence on teacher performance. Keywords: Work Discipline, Work Motivation, Work Environment, Career Development and Teacher Performance